About inclusions found in erythrocytes of some lizards (Lacertilia - sp) A new Bartonella? - Weiss, Pedro (1927)
Suggestibility by the widespread belief among the inhabitants of some warty and utosas areas involving a reptile in the cycle of these diseases, I have tried repeatedly to examine the blood of animals in such order, both in endemic areas and in other places.